2022
DOI: 10.33776/amc.v48i178.7405
|View full text |Cite
|
Sign up to set email alerts
|

The five C-S of positive youth development and life purpose among Roma and Egyptian minority adolescents in Albania

Abstract: The 5Cs model of Positive Youth Development focuses on thriving adolescents who develop positivequalities, which are known to help them deal with challenges, tasks, and psychological concerns. LifePurpose acts as a protective factor in relation to the general well-being of adolescents and supports the5Cs through this process of growth. The aim of this study is to examine the role of the 5Cs of PYD, namelyCompetence, Confidence, Connection, Caring, and Character, and how Life Purpose is explained by the 5Cs. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…Indeed, Miconi et al (2021a) reported that discrimination from peers and teachers were common experiences among Egyptian and Roma youth in Albania, and that schools were often perceived as unsafe and violent places. The segregation of Roma and Egyptian children and adolescents in schools is common in Albania and represents a timely and hot political issue in the country ( Dervishi et al, 2021 ; Likmeta, 2022 ; Taylor, 2022 ). It is urgent that the structural violence, segregation and marginalization of Roma and Egyptian communities in Albania and in Europe are acknowledged and addressed by prevention and intervention efforts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, Miconi et al (2021a) reported that discrimination from peers and teachers were common experiences among Egyptian and Roma youth in Albania, and that schools were often perceived as unsafe and violent places. The segregation of Roma and Egyptian children and adolescents in schools is common in Albania and represents a timely and hot political issue in the country ( Dervishi et al, 2021 ; Likmeta, 2022 ; Taylor, 2022 ). It is urgent that the structural violence, segregation and marginalization of Roma and Egyptian communities in Albania and in Europe are acknowledged and addressed by prevention and intervention efforts.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, although there was a reduction in school drop-out, rates still remain the highest in the country, with 1 to 5% of Egyptian and Roma people who have completed secondary education versus 94.5% for the overall population in Albania ( Home Office, 2017 ; Psacharopoulos, 2017 ). Noteworthy, the pandemic represented an additional risk factor for school drop-out among Egyptian and Roma adolescents who were still enrolled in school because of barriers in attending online classes due to lack of internet connection and space at home ( Dervishi et al, 2021 ; Miconi et al, 2021a ).…”
Section: Introductionmentioning
confidence: 99%